Brain Drain in Nigerian Health Sector: An Unsung Epidemic - Olowolaju OF; Akpor OA; Adeoluwa OA (RGUHS Journal of Nursing Sciences)
Brain drain in the Nigerian health sector is a critical issue that has drained Nigeria of skilled and competent healthcare professionals thereby placing a heavy burden on the Nigerian healthcare system. The paper aimed to describe some factors responsible for the increase in brain drain and thereby offer possible solutions to the problem. The theory of push and pull factors was used to describe the phenomenon. Push factors are unfavourable conditions that push people out of their domain country while pull factors are favourable conditions that attract citizens to migrate to developed countries. The consequences of brain drain in the health sector led to the shortage of skilled healthcare workers which places a heavy burden on those who remain leading to increased workload and burnout. The paper also highlighted various efforts the Nigerian government had put in place to mitigate the effects of brain drain in Nigeria such as implementation of the national health policy increased funding for the health sector and strengthening of healthcare institutions. Unfortunately the efforts are yet to yield positive impacts. However this paper has several possible recommendations aimed at reversing brain drain in the health sector which include improvement of working conditions and remuneration development of retention strategies to retain healthcare professionals and addressing socioeconomic factors that contribute to brain drain. The study concluded that brain drain in the Nigerian health sector is a significant challenge that requires urgent attention and a multifaceted approach. Only then can Nigeria hope to alleviate the unsung epidemic of brain drain in its health sector.